The Influence of Work Ability and Workload Towards the Employee Performances and Work Stress as the Mediation Variable in the General Election Supervisory Agency Located in DKI Jakarta Province - Haning Wijayanti; Deden Kurniawan (Budapest International Research and Critics University, 2022)
This research aims to analyze the effect of work ability and workload on the employee performance and work stress as a mediation variable in the General Election Supervisory Agency in DKI Jakarta. The population of this study were Non-Government Employees with a sample of 100 employees. Data analysis method used structural Equation model Partial Least Square (SEM-PLS). The results revealed that the variables of work ability affected the variable of work stress negatively and significantly. The workload variables affected the work stress variable positively and significantly. Work stress variables affect negative employee performance but not significantly. Meanwhile, variable work ability affects positive employee performance and significantly. Besides, workload variables affect positive employee performance but not significantly.